Resonator researches of accelerating system of the applied ion installations - Svistunov, Yu.; Budtov, A.; Mudrolubov, V.; Petrov, V.; Silaev, S. (Вопросы атомной науки и техники, 2004)
33 MHz RFQ and APF-cavity construction, manufacture and tuning are considered. These resonators are developed at the D.V. Efremov Institute for applied complexes where ion beams are used. In particular, there are considered proton and deuteron versions of the contraband detection complex with linac. Computer results of simulation of electromagnetic and thermal fields in resonators are given. Calculations of the cooling system and possible structure deformations in consequence of mechanical and thermal tensions are presented.